The Symbolic Meaning of Sikambang Anak Dance at the Upik Berau Studio, Air Berau Village, Mukomuko Regency, Bengkulu Province - Juniarti, Tira Rofi; Erlinda; Surherni (Regalia Institute, 2024)
This research aims to determine the symbolic meaning of the Sikambang Anak dance at the Upik Berau Studio, Air Berau Village, Mukomuko Regency, Bengkulu Province. The research method used is a qualitative research method which is descriptive analysis, namely explaining and describing what is then analyzed. This research uses Ferdinand De Saussure's semiotic theory and Y. Sumandiyo Hadi's theory of form. The results of the research show that the symbolic meaning of the Sikambang Anak Dance at the Upik Berau Studio has its own meaning for the people of Air Berau village. The meaning conveyed can be seen from the form of the sikambang anak dance itself, starting from the movements. Properties and poetry (dendang). This dance has a meaning related to people's lives. The meaning of this dance teaches that problems in married life will be better if they are resolved amicably and don't make the wrong decisions. Kindness is always at the forefront of life